(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The purpose of the article is to discuss about a stylistic device which is called “allegory” and its origin. Moreover, it shows that “allegory” can be mentioned as both stylistic device and literal device. Also, this is a great stylistic tool which has two classical and religious types.